Farmers' preferences of cattle breeds, their market values and prospects for improvement in West Africa: A summary review - Kamuanga, M.; Tano, K.; Pokou, K.; Jabbar, M.A.; D'Ieteren, G.D.M. (OAU/STRC, 2001)
There is a broad land of territory comprising the subhumid zone and the non-forested areas of the humid zone of West Africa in which a mixture of trypanotolerant, trypano-susceptible, and crossbred cattle are found. Availability of a variety of breeds allows farmers to choose the breeds they judge most appropriate for their circumstances. From the perspective of the national and international community, however, there is a risk that valuable strains or breeds of cattle may be interbred out of existence, as indicated by the current downward trend in the population of some indigenous trypanotolerant breeds, following the continued incursion of disease-prone Zebu cattle into the subhumid, tsetse-infested zones in the region. The case studies reviewed here were conducted between 1994 and 1997 by 1LRI research teams in Burkina Faso, Cote d'Ivoire and Nigeria to evaluate farmer preferences for cattle traits. The objectives were to obtain information necessary for a possible reorientation of cattle improvement programmes and to determine factors affecting adoption and conservation of trypanotolerant cattle at risk of extinction. In Burkina Faso and Cote d'Ivoire, farmers preferences for cattle traits were evaluated using the technique of conjoint analysis. Fitness to traction, disease resistance and fertility were found to be the most preferred traits of bulls. Most preferred traits for cows were fecundity, disease resistance and feeding ease. Analysis of the relationships between breed preferences and breeding practices confirmed a strong trend away from Muturu (southwest Nigeria) and Baoule (southern Burkina Faso) - two West African shorthorn cattle known to be trypanotolerant-and identified the traits farmers find less desirable and traits more desirable relative to other breeds. Importantly, high preferences for disease resistance and relatively low preferences for standard off-take traits (milk and beef) suggest that indigenous breed preservation in situ and planned programmes for cattle breed improvement are both possible. In all three countries, analysis of cattle market prices found small, but significant, price differences by breed.